Efforts to Improve Student Learning Outcomes in Islamic Education Learning through Storytelling Methods at MI Unggulan Al-Fadel Bogor - Lidya, Yayah; Budiyanti, Yeni (Indonesian Journal of Education and Social Humanities, 2024)
This study aims to see the impact of using the storytelling method to increase students' interest in learning and activeness and improve student learning outcomes in Islamic Religious Education learning about distinguishing good and bad morals in class I students of MIS Unggulan Al Fadel Sasak Panjang, Bogor. The study used classroom action research with 2 cycles with each cycle stage being planning, action, observation, and reflection. Data collection was carried out through observation of the teaching and learning process and documentation of the results of the actions taken. The results of this study indicate an increase in students' interest in learning Islamic religious education about morals through the storytelling method, this can be seen from the results of observations of students' interest in learning in cycle I 63% increasing to 94% in cycle II. The results of research on student activeness in learning have also shown an increase from 57% of students who have good activeness in cycle I to 89% in cycle II. Likewise, research on student learning outcomes increased by 47% of students who have good learning outcomes in cycle I, to 74% in cycle II. The storytelling method can improve the learning outcomes of class I students of MIS Unggulan Al Fadel Sasak Panjang, Bogor in learning Islamic religious education about morals for students and can improve students' abilities in distinguishing between good and bad morals or actions.